Digital Finance, ESG Integration dan Financial Stability: A Systematic Literature Review - Saripudin (JURNAL ILMIAH EDUNOMIKA, 2025)
Digital transformation is reshaping the financial sector and directly influencing both financial stability and the implementation of sustainable finance. However, empirical findings remain mixed, particularly regarding the mediating or moderating role of ESG integration. This study conducts a Systematic Literature Review (SLR) following the PRISMA 2020 protocol to synthesize 20 relevant studies from an initial pool of 1,248 articles identified across Scopus, Web of Science and Google Scholar. The findings indicate that digitalization enhances efficiency, financial inclusion, and sustainability performance, though it simultaneously introduces cyber risks and regulatory uncertainties. ESG integration reinforces stability through stronger risk governance and transparency. Overall, the study highlights that synergy between digitalization and ESG is essential for building a stable, inclusive, and sustainable financial system and provides a conceptual foundation for subsequent empirical research.